A boundary element method formulation to capture strong discontinuities in solids - Manzoli, Osvaldo L.; Venturini, Wilson S. (My University, 2005)
A Boundary Element Method (BEM) formulation to predict the behavior of solids exhibiting displacement (strong) discontinuity is presented. In this formulation, the effects of the displacement jump of a discontinuity interface embedded in an internal cell are reproduced by an equivalent inelastic strain field in the cell. As a consequence, the non-linear BEM integral equations that result from the proposed approach are similar to those of the implicit BEM based on initial strains, so that only small changes in the standard implicit boundary element codes are required to make possible strong discontinuity simulations. Since discontinuity interfaces can be introduced in the interior cell independently of the cell boundaries, the proposed BEM formulation allows for arbitrary discontinuity propagation using a fixed internal cell mesh. A concrete fracture test is analysed to access the performance of the proposed formulation.
Keywords: Boundary elements; Crack; Fracture mechanics; Strong discontinuity